Alert System to Prevent Drowning using IoT- A Survey - Amshavalli, M.; Nandhini, A.; Sathiya, S.; Sheelamani, M. (Journal of ISMAC, 2024)
Swimming is a popular sport as it is a pleasant recreational hobby. Aside from its physical benefits, it also relieves stress and gives a sense of peace. So, it is highly preferred by children’s, adults, and sometimes even elderly people. Many countries have made swimming and other life skills compulsory activities in school to avoid fatalities in the event of disaster. While swimming has many advantages, safety precautions are paramount to avoid unintentional deaths. While various drowning prevention systems and technologies have been developed, many of them lack accuracy in detecting drowning incidents and fail to provide an effective rescue mechanism for swimmers in distress. To develop a smart anti-drowning and alert system, this study presents a comprehensive survey of existing drowning systems and suggests a proposed model in response to the identified gaps and challenges in current systems. The suggested framework includes Arduino microcontrollers, voice recognition technology, ultrasonic sensors, and alert generators. The proposed approach not only addresses the constraints of existing systems, but it also provides a cost-effective and scalable solution that can be used in a variety of water environments, including pools and natural bodies of water. The suggested system has the potential to reduce reaction times in emergency circumstances, adding to the overall enhancement of water safety. Future research could focus on practical implementation, testing, and improvement of the proposed model to improve its usefulness in reducing drowning accidents.